Development of a prototype wireless charger - Lam, Luke Weng Keong (2018)
The convenience of wireless charging coupled with a green energy source makes it a promising idea. This is especially so in the quest for a sustainable earth that is increasing in the demands for the use of energy year after year. Wireless power transfer, is the transmission of electrical energy without the usage of any wires. The techniques for wireless power transfer mainly fall into two categories, they are near-field and far-field power transfer. For the former, the transfer of power is over short distances via magnetic fields between coils of wire, using inductive coupling. For the latter, the transfer of power is over longer distances. As the project is about wireless power transfer with relation to mobile phones, we will be focusing on near-field power transfer. Solar power is the conversion of energy attained from sunlight, into electricity. Via the photovoltaic effect, photovoltaic cells convert light into an electric current. In this day and age, we still depend very heavily on fossil fuels for energy. The usage of non-renewable sources of energy such as fossil fuels, leads to the production of greenhouse gases. Greenhouse gases are a major contributor to global warming, and it is essential to look for ways to reduce the production of it. Some advantages of having solar powered wireless chargers are that, it not only adds a touch of convenience, but it also ensures that we consume energy responsibly by using renewable energy to charge our phones. Also, in the long run, it helps to save monetary cost on energy required for phone usage. Solar powered wireless chargers can also be used in many other applications. For example, you can wireless charge smart-watches, tablets, and even electronic cars. For this project a prototype of a solar powered wireless charger will be designed. With this prototype, we will be able to further investigate how we can increase the efficiency and performance, which could prove to be useful for future works